GROWTH RATES OF LATITUDE AND CIRCULARITY INDICATORS OF THE BODY IN PRESCHOOL CHILDREN AGED FROM 4 TO 6 YEARS - Roza T. Kamilova; Aygul Zh. Ilyasova (Central Asian Journal of Medicine, 2024)
Research was carried out on state preschool educational organizations (SPEOs) in Tashkent and Surkhandarya region, built from different building materials: light metal structures, reinforced concrete and baked brick. 474 children aged 4 to 6 years were examined, of which 231 were boys and 243 were girls. The children were divided into three groups: the 1st and 2nd groups attended the SPEOs made of light metal structures and reinforced concrete, and the control group - made of baked brick. The results showed that children from preschool educational institutions built from baked bricks had higher rates of growth in physical development compared to children from other groups, emphasizing the importance of the choice of building material for education.